Freedom arrives : what next for the LCS? - Graham, Euan (2014)
As the first-built Littoral Combat Ship, and the first to be deployed from Singapore, the USS Freedom carries high expectations for the US Navy and the US "re-balance" to Asia. How will this capability be received regionally, and what are the implications for maritime security?